PENERAPAN PENDEKATAN SAINTIFIK MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI POTENSI SUMBER DAYA ALAM DAN KEMARITIMAN INDONESIA SISWA KELAS VII SMP DARUSSA’ADAH PUTRI - Nuraini Nuraini (Jurnal Sosial Humaniora Sigli, 2020)
This study aims to describe student learning activities and student learning outcomes by applying the Scientific Approach to the Discovery Learning Model in the material of the Potential of Natural Resources and Maritime. This classroom action research was carried out in two cycles. Each cycle consists of four stages, namely planning, implementing actions, observing, and reflecting. The subjects in this study were seventh grade students of Darussa’adah Putri Middle School in the 2015/2016 academic year, with 24 students consisting of 7 female students and 17 male students. Data collection techniques used are test and non-test techniques. Data analysis was performed by quantitative data analysis the average formative test value of the first cycle of 61.46 increased in the second cycle to 77.50. Classical learning completeness in the first cycle of 38% increased in the second cycle to 92%. Thus, it can be concluded that the application of the scientific learning model discovery learning model can improve student learning outcomes in the material of the Potential of Natural Resources and Indonesian Maritime in class VII students of Darussa’adah Putri Middle School. Therefore, teachers are advised to apply the scientific model of discovery learning models in social studies learning or other lessons. Keywords: Scientific Discovery Learning Model, Learning Outcomes